Updating Ceramium (Rhodophyta, Ceramiales) biodiversity in the North Adriatic Sea (Mediterranean): Ceramium rothianum sp. nov. and rediscovery of three forgotten species. Issue 4 (2nd October 2019) - Wolf, Marion A.; Sciuto, Katia; Betto, Viola M.; Moro, Isabella; Maggs, Christine A.; Sfriso, Adriano
ABSTRACT: The cosmopolitan genus Ceramium Roth (Ceramiaceae), with over 200 currently accepted species, is one of the largest in the Rhodophyta. The genus is characterized by cylindrical or slightly compressed thalli, with axial cells incompletely to completely covered by cortical cells, alternate to pseudo-dichotomous branching and straight to inrolled apices. Despite recent studies, the nomenclature and taxonomy of this genus are still very problematic, linked to the high degree of variation in morphological characters, small thallus sizes, epiphytic habit and the existence of cryptic species. The Mediterranean Sea is reported to have a particularly high diversity of Ceramium species: the North Adriatic Sea, in particular Venice and nearby coasts, was a favourite classical collecting area from where several species were described. In this study we characterize Ceramium sampled from transitional waters of the Venice Lagoon (Italy) by molecular and morphological approaches. Through phylogenetic analyses, using the plastid ribulose-1, 5-bisphosphate carboxylase/oxygenase gene ( rbc L) as molecular marker, we identify six distinct taxonomic entities, of which four represent taxa not currently recognized in the Venice Lagoon or the wider Mediterranean Sea. One of these is the poorly known species Ceramium connivens Zanardini, which is non-spiny and fully corticated when mature with short naked internodes developing in older axes. Two entities with erect partially corticated thalli without spines, probably misidentified up to now as Ceramium diaphanum (Lightfoot) Roth, correspond to the new species Ceramium rothianum Wolf et al . and to the forgotten species Ceramium nodosum (Kützing) A.W. Griffiths & Harvey. The last entity, characterized by prostrate axes giving rise to narrow erect incompletely corticated, non-spiny axes, is identified as the rare, poorly known species Ceramium incospicuum Zanardini.